(x+5-2i)(x+5+2i) how do I work this out I can not remember please show me how to find the answer thanks!

1 Answer | Add Yours

Top Answer

embizze's profile pic

embizze | High School Teacher | (Level 1) Educator Emeritus

Posted on

Expand `(x+5-2i)(x+5+2i)`

We use the extended distributive property:

`(x+5-2i)(x+5+2i)`

`=x^2+5x+2ix+5x+25+10i-2ix-10i-4i^2`

`=x^2+10x+25-4i^2` (but `i=sqrt(-1)=>i^2=-1` so)

`=x^2+10x+29`

Thus `(x+5-2i)(x+5+2i)=x^2+10x+29`

We’ve answered 318,994 questions. We can answer yours, too.

Ask a question